A new approach to production of mass suppliable water purifier - Afizi Mohd Shukran, Mohd; Pak, Hunkyun; Nazri Mohd Ismail, Mohd; Maskat, Kamaruzaman; Abu Ubaidah Amir Abu Zarim, Mohammad; Shazwani Abdul Latif, Nur; Hakimi Ahmad Zainudin, Mohd; Ariff, Hafizah (International Journal of Engineering and Technology, 2019)
Potable water can be produced from untreated water sources using variety of water purification techniques. In a critical situation such as flood, some of the technique such as heating the water might not be possible especially when the water level had increased to an alarming rate. The flood victims might be threaten by water-borne diseases which make them to suffer from illness, and in a worst case might lead to death. The development of low cost and simple water purifier without the use of fuel energy is very helpful in this situation. A simple sand and charcoal filter such as PAK filter together with solar disinfection (SODIS) method has been proven effective in killing the micro-organism and blocks the chemical contaminants which are dangerous from being consume by the flood victims. This paper will introduced some of the methods such as water filtration technique and sterilization that can be practiced by the flood victims in order for them to survive during flood.Â